Synthesis of polylactide: Effect of dispersion of the initiator - Kaur P.; Mehta R.; Berek D.; Upadhyay S.N. (My University, 2025)
The ring opening polymerization of L-lactide was studied in bulk using stannous octoate as initiator. In some experiments, triphenylphosphine, a Lewis base was also used as co-initiator. The polymerization was carried out at 130C up to 29 h. The monomer was used after recrystallizing three times with dry toluene. Experiments were carried out using a wide range of monomer to initiator ratio. The averages and distributions of molar masses of resulting PLA have been determined by means of size exclusion chromatography, SEC. It is shown that the (mode, process) procedure of dispersion of the catalyst in polymerization system affects the molar mass distribution of the product as is evidenced by the bimodality or even trimodality observed in the SEC chromatograms. © 2011 Taylor & Francis Group, LLC.